Keuangan Publik dan Sosial Islam: Peran dan Mekanisme Pengawasan Pemerintah terhadap Kegiatan Ekonomi dalam Perspektif Islam - Deni Arnandi; Deno Deno; Selbia Albina; Thamara, Thamara Putri Andina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study describes Islamic public and social finance: the role and mechanisms of government oversight of economic activities from an Islamic perspective. The purpose of this study is to explain Islamic public and social finance: the role and mechanisms of government oversight of economic activities from an Islamic perspective. The research method is qualitative. Data analysis was conducted using thematic analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. This research finds that the government's role from an Islamic public and social finance perspective is not only as a regulator but also as an active supervisor, ensuring that economic activities are run in accordance with Sharia principles. Supervisory mechanisms are implemented through the institution of hisbah (Islamic tax), Sharia-based regulations, and a system of public financial accountability and transparency. Furthermore, Islamic social finance instruments such as zakat (alms), infaq (donations), sedekah (charity), and waqf (endowments) have been proven to play a role in equitable wealth distribution and reducing social inequality. This supervisory concept remains relevant in the modern economic context, including the digital sector and Sharia finance. The implications of this research suggest that the government needs to strengthen the implementation of Islamic-based supervision in the modern economic system by strengthening Sharia financial institutions, optimizing the management of Islamic social funds, and enhancing transparent and accountable regulations. Furthermore, adaptation of Islamic supervisory mechanisms is necessary to address the development of the digital economy. This research also implies the importance of increasing Sharia economic literacy among the public to support the creation of a more sustainable and equitable economic system.